Introducing an integrated maternity care pathway for women with a history of small-for-gestational-age: Evaluation of its effect on care process and clinical outcomes - Anne C. M. Hermans; Julia Spaan; Marieke A.A. Hermus; Amber M. Hietkamp; Jantien Visser; Arie Franx; Jacoba van der Kooy (PLoS ONE, 2026)
Introduction This study focusses on the implementation of an integrated care pathway for women with SGA in their obstetric history that pursues value-based healthcare. This study aims to 1) Determine whether the integrated care pathway led to a reduction in the number of antenatal secondary care consultations, as an indicator of care efficacy, and 2) compare clinical outcomes for women with a history of SGA before and after implementation of the integrated care pathway. Methods Retrospective cohort study including data from pregnant women with a history of SGA within integrated maternity care organisation Annature, 2017–2020. Intervention was an integrated care pathway (2018). Pre- and post-intervention periods were compared assessing prenatal secondary care consultations, place and mode of delivery, and perinatal outcomes. Results The implementation of the care pathway for pregnant women with a history of SGA led to a reduction in mean number of prenatal secondary care consultations per pregnancy from 11 in 2017–5 in 2020, and fewer inductions of labour (78 (34.2%) vs 127 (26.8%), p = 0.045). Additionally, the number of births in primary care increased (35 (15.4%) vs 136 (28.8%), p < 0.001) with no significant adverse impact on neonatal outcomes in the post-intervention period compared to the pre-intervention period. Conclusion The implementation of the care pathway for pregnant women with a history of SGA resulted in a reduction in prenatal secondary care consultations and fewer inductions of labour. Additionally, the number of births in primary care increased, with no significant adverse impact on neonatal outcomes in the post-intervention period compared to the pre-intervention period.